Brutes: A Novel - Tate, Dizz (New York : Catapult, 2023)
A group of teenage girls discover a dark secret about their fame-hungry Florida town that will haunt them for the rest of their lives when their friend, the local preacher's daughter, Sammy, goes missing.
Keywords: Teenage girls -- Fiction; Missing persons -- Fiction; Florida -- Fiction